2020
DOI: 10.1021/acs.analchem.9b05849
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensing of Exosomal MicroRNA Based on Hybridization Chain Reaction Signal Amplification with Reduced False-Positive Signals

Abstract: MicroRNAs (miRNAs) in cancer cell-derived exosomes are important cancer biomarkers. Herein, a sensitive hybridization chain reaction (HCR) electrochemical assay was fabricated for the detection of exosomal microRNA-122 (miR-122). The hairpin DNA (hpDNA) probes were first immobilized on the surface of a gold electrode. In the presence of miR-122, the hairpin structure of the hpDNA could be opened and triggered the HCR through the cross-opening and hybridization of two helper DNA hairpins. Long nicked double hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 52 publications
0
66
1
Order By: Relevance
“…This simple DNA structural transformation could detect exosomal miR-21 with a LOD as low as 2.3 fM. Guo et al showed a sensitive electrochemical assay of miR-122 by HCR of the hairpin structure of the capture DNA on the surface of the electrode [91]. The miR-122 opened the hairpin DNA and triggered the HCR through the cross-opening and hybridization of two helper DNA hairpins.…”
Section: Electrochemical-based Analysis Methods For Ev Detectionmentioning
confidence: 99%
“…This simple DNA structural transformation could detect exosomal miR-21 with a LOD as low as 2.3 fM. Guo et al showed a sensitive electrochemical assay of miR-122 by HCR of the hairpin structure of the capture DNA on the surface of the electrode [91]. The miR-122 opened the hairpin DNA and triggered the HCR through the cross-opening and hybridization of two helper DNA hairpins.…”
Section: Electrochemical-based Analysis Methods For Ev Detectionmentioning
confidence: 99%
“…According to the authors, this method is highly sensitive, cheap, and results are reproducible. However, their assay was not used yet to analyze patient samples [149].…”
Section: Applications Of Surface-enhanced Raman Scattering (Sers) Basmentioning
confidence: 99%
“…Boriachek et al 26 prepared DNA-modified magnetic beads for the capture and amplification-free measurement of the target. Guo et al 27 achieved DNA elongation on the electrode interface by hybridization chain reaction and determined exosomal miRNA levels with reduced false-positive signals.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with some other nonenzymatic amplifications, like the hybridization chain reaction, the distance between electrochemical species and electrode is not only closer but also fixed, which is more suitable for quantitative analysis. 27…”
Section: Introductionmentioning
confidence: 99%